(untitled) - Tung, Chih-Hang (Hoboken, N.J., 2003)
Ultra Large Scale Integration (ULSI)_refers to chips with_more than 10,000,000 devices per chip. It is the natural outgrowth of VLSI (Very Large Scale Integration). ULSI Semiconductor Technology Atlas uses TEM (Transmission Electron Microscopy) micrographs to explain and illustrate ULSI process technologies and associated problems.
Keywords: Integrated circuits,Electron microscopy,Mạch tích hợp,Kính hiển vi điện tử; Ultra large scale integration,Ultra tổ hợp quy mô lớn